The Role of Knowledge Creation to Improve SMEs Performance in COVID-19 Era based on Knowledge Oriented Leadership and Value of Knowledge Congruence - Damayanti, Adelia Ika; Ferdianto, Raditya; Rahayu, Indah (CV. Strata Persada Academia, 2025)
This study investigates the role of Knowledge Creation (KC) through the SECI process in enhancing SMEs' performance, especially during the shift to online business activities amid the COVID-19 pandemic. SMEs need adequate knowledge and adaptability to survive and contribute to economic growth. This research proposes a model where KC, facilitated by digital technology, operates through the SECI process with support from Knowledge-Oriented Leadership (KOL). Effective knowledge sharing between leaders and members fosters the Value of Knowledge Congruence (VOKC), aligning organizational goals and improving performance. Using an explanatory quantitative approach, data were collected from 100 SMEs in Central Java (Semarang, Pekalongan, Rembang, and Jepara) through questionnaires. Data were analyzed using Partial Least Square (PLS). Results show that KOL significantly influences KC in the SECI process. Externalization and internalization positively and significantly affect VOKC, while socialization and combination have positive but insignificant effects. VOKC significantly enhances SMEs' performance, highlighting the importance of KC through the SECI process and leadership in driving SMEs' success in dynamic environments.